THE PATH TO SUSTAINABLE DERADICALIZATION PROGRAM - Walanda, Garnadi (UI Scholars Hub, 2020)
Deradicalization program is a never-ending challenge for any country to pursue the most viable model, which actually can be done by enhancing the different methods from one country to another. Deradicalization is also a challenge for multidisciplinary research to continue to understand the various phenomena of terrorism and how to integrate their response solutions into a definitive program. The author conducts a qualitative study on contemporary literature and various researches on deradicalization program and approaches that can be used and sustain in this country. This article is presenting the comparison as well as advantages and deficiencies of the implementation of global deradicalization programs from (five) regions, namely in the America, Europe, the Middle East, Africa, and Asia. The results shown that a concrete form of deradicalization and disengagement program under public private partnership scheme is possible to be implemented in a comprehensive and sustainable manner.